Pengaruh Work Life Balance Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Kependudukan Dan Catatan Sipil Kota Makassar - Isnaeni, St. Nur Amaliah Nandita; Anggoro, M. Yusuf Alfian Rendra; Asdar, Asdar (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to determine and analyze the influence of Work Life Balance and Work Environment on Employee Performance at the Population and Civil Registration Office of Makassar City. The type of research used is quantitative research. Data collection techniques were carried out through observation, questionnaires, and documentation. The population in this study consisted of 54 individuals, and the sampling technique used was the saturated sample method. The data sources used consisted of primary and secondary data. Data analysis was conducted using multiple linear regression with the help of SPSS version 25. The results of the study indicate that: Work Life Balance (X1) has a positive but not significant effect on employee performance at the Population and Civil Registration Office of Makassar City, with a variable coefficient of 0.225 and a significance value of 0.061, which is greater than 0.05 (0.061 > 0.05). Meanwhile, the Work Environment (X2) has a positive and significant effect on employee performance at the same office, with a variable coefficient of 0.358 and a significance value of 0.032, which is less than 0.05 (0.032 < 0.05).